(untitled) (Agro Productividad, 2021)
Objective: To evaluate the effect of NPK fertilization on the chemical properties and bioactive compounds of the cabezona pineapple fruit. Design/methodology/approach: 15 NPK fertilization treatments were evaluated and carried out in the field in a random complete block design with four repetitions per treatment. At the end of the crop cycle, we determined the pH, °Brix and citric acid % of the fruits that were harvested, following the methodology established in NMX-FF-028 and 011. The pH of the juice was measured directly using a potentiometer. Ascorbic acid was measured with a SIGMA-ALDRICH® kit, the total polyphenol contents were determined following the methodology of De la Cruz-Ricardez et al. (2020), while total flavonoid contents were measured following a modified version of the methodology proposed by Hossain et al. (2011). Results: The mean values for °Brix, citric acid %, and pH were 7.3, 7.1 and 3.4 respectively, without significant differences between treatments. A highly significant difference in the concentration of ascorbic acid was observed between treatments; treatment three had the highest concentration (19.4 mg 100 g-1 FF). There were no significant differences between the fertilization treatments and the control, regarding total polyphenol content (41.34 mg 100 g-1 FF) and flavonoids (1.6 mg 100 g-1 FF) concentrations. Study limitations/implications: The ripening degree of the pineapple fruit directly influences the chemical properties and the concentration of bioactive compounds. Findings/conclusions: NPK fertilization had no effect on °Brix and pH. The citric acid percentage and the total polyphenol content increased as the doses of P2O5 increased. The ascorbic acid concentration and total flavonoid content are not affected by the NPK fertilization dose.